Olive Oil Attenuates the Cholesterol-induced Development of Nonalcoholic Steatohepatitis Despite Increased Insulin Resistance in a Rodent Model - Buettner, R.; Ascher, M.; Gäbele, E.; Hellerbrand, C.; Kob, R.; Bertsch, T.; Bollheimer, L. C. (Hormone and Metabolic Research, 2013)
It is indefinite whether nonalcoholic steatohepatitis (NASH) results as by-product from general metabolic perturbations and adipokine dysregulations or whether defined dietary factors also play a pathogenetic role. Here, we examine the effects of a modification of dietary lipids in a NASH inducing diet on metabolic changes as well as hepatic steatosis, inflammation, and fibrosis in rats. Male Wistar rats were fed with variations of the atherogenic diet (AD), which induces pathophysiological changes resembling human NASH. Dietary variants (AD without cholesterol, cholate, or choline; change of neutral fat to olive oil or coconut oil) were fed for 8 weeks. Insulin resistance, adipokine profile, liver histology, and lipid content as well as expression of proinflammatory and profibrogenic genes were examined. AD led to clear signs of hepatic steatosis and inflammation together with an increase in TNF and collagen type 1 expression. AD without cholesterol showed markedly less liver damage without changes of insulin action and adipokine profile. AD with olive oil and AD without cholate clearly attenuated hepatic inflammation, whereas fat deposition and features of the metabolic syndrome were increased in these animals. Insulin resistance and hepatic fat deposition per se do not cause significant hepatic inflammation in this rodent model. However, dietary cholesterol is an important causal agent for the development of NASH. Olive oil plays a protective role in this respect, which might be due to the high content of monounsaturated fatty acids.
Keywords: nonalcoholic steatohepatitis; atherogenic diet; insulin resistance